Contemporary sacred spaces. Towards a rigorous study of architectural experience - Puertas, Alvaro (2023)
Sacred spaces are places for celebration, meeting and conversation. In that sense, they enhance the best of human relationships, embodying the spirit of the tinkuy. To better understand them, it is important to cultivate interdisciplinarity, studying the architec- tural experience with the support of cognitive sciences. Despite the complexity in the dialogue with other disciplines, we rely on neurophenomenology to identify mental and physical patterns of the subjects who navigate in sacred spaces. Thanks to Christopher Alexander’s pattern language, we complete the triad of mind-body-environment patter- ns that, by validating each other, allow us to corroborate whether a space is sacred, sig- nificant or architectural.